2021
DOI: 10.3390/jcm10081781
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Analgesic Efficacy of a Bioelectronic Device in Non-Specific Chronic Low Back Pain with Neuropathic Component. A Randomized Trial

Abstract: Low energy pulsed electromagnetic signals (PEMS) therapy, in the field of bioelectronics, has been suggested as a promising analgesic therapy with special interest in treating conditions with poor response to pharmacotherapy. This study evaluated the effectiveness of PEMS therapy on the treatment of chronic low back pain patients with a neuropathic component. A group of 64 individuals with such condition was allocated to a 2-week treatment period (10 twenty-minute sessions on consecutive days) with an active P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
(84 reference statements)
0
0
0
Order By: Relevance
“…Significant improvements were reported in the ODI scores of the PEMFT group compared to the sham group from the baseline to the sixth week, which continued through the 12th -week follow-up [ 24 ]. In a study by Teresa et al [ 25 ], low-energy PEMFT was found to improve neuropathic pain and functional status in chronic low back pain with a neuropathic component, compared to the control group. In a systematic review and meta-analysis of 14 studies, PEMFT significantly reduced low back pain compared to a placebo and other treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Significant improvements were reported in the ODI scores of the PEMFT group compared to the sham group from the baseline to the sixth week, which continued through the 12th -week follow-up [ 24 ]. In a study by Teresa et al [ 25 ], low-energy PEMFT was found to improve neuropathic pain and functional status in chronic low back pain with a neuropathic component, compared to the control group. In a systematic review and meta-analysis of 14 studies, PEMFT significantly reduced low back pain compared to a placebo and other treatments.…”
Section: Discussionmentioning
confidence: 99%
“…General HRQoL is measured in patients with NSLBP mainly by using a 12-or 36-item Short Form Health Survey version 2 (SF-12; SF-36) questionnaire. HRQoL domain scores have been found to improve after the following: 5 weeks of massage therapy, therapeutic exercise, and a therapeutic education program [13]; therapeutic ultrasound in addition to exercise [2]; minimally invasive treatment [6]; invasive laser acupuncture [14]; negative pulsed-pressure myofascial vacuum therapy [15]; photobiomodulation therapy using low-intensity Light Amplification by Stimulated Emission of Radiation (LASER) and light-emitting diodes [16]; continuous, low-level heat therapy [17]; Medi-Taping [18]; low-energy pulsed electromagnetic signals therapy [19]; pulsed electromagnetic field therapy [20]; exercises on a Pilates mat and home exercise programs [21]; traditional Thai self-massage combined with home stretching exercises [22]; wholebody vibration [23]; and mountain hiking combined with Mg-Ca-SO 4 spa therapy [24]. Moreover, core stability exercises (CSE) combined with self-compassion training were more effective for patients with non-specific chronic low back pain compared to CSE alone [25].…”
Section: Introductionmentioning
confidence: 99%